2016
DOI: 10.1038/ijos.2016.24
|View full text |Cite
|
Sign up to set email alerts
|

Current advances in orthodontic pain

Abstract: Orthodontic pain is an inflammatory pain that is initiated by orthodontic force-induced vascular occlusion followed by a cascade of inflammatory responses, including vascular changes, the recruitment of inflammatory and immune cells, and the release of neurogenic and pro-inflammatory mediators. Ultimately, endogenous analgesic mechanisms check the inflammatory response and the sensation of pain subsides. The orthodontic pain signal, once received by periodontal sensory endings, reaches the sensory cortex for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
108
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 120 publications
(134 citation statements)
references
References 143 publications
(175 reference statements)
3
108
0
6
Order By: Relevance
“…Our results, along with those of previous studies and hypotheses, indicated that the gray matter of the limbic system is prone to damage in patients with chronic MTrPs-related pain, and that these abnormalities may be pertinent to patients’ pain perception and emotional changes. Moreover, Recent investigations have indicated that the ACC may be involved in the processes of pain and emotion (Vogt, 2005) and that other cerebral areas, such as the hypothalamus and the amygdaloid nucleus, may play an important role in regulating emotion (Blouin et al, 2013; Long et al, 2016). However, decreased DKI parameters in the hypothalamus and the amygdaloid nucleus were not observed in our experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Our results, along with those of previous studies and hypotheses, indicated that the gray matter of the limbic system is prone to damage in patients with chronic MTrPs-related pain, and that these abnormalities may be pertinent to patients’ pain perception and emotional changes. Moreover, Recent investigations have indicated that the ACC may be involved in the processes of pain and emotion (Vogt, 2005) and that other cerebral areas, such as the hypothalamus and the amygdaloid nucleus, may play an important role in regulating emotion (Blouin et al, 2013; Long et al, 2016). However, decreased DKI parameters in the hypothalamus and the amygdaloid nucleus were not observed in our experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Conventionally, the pain management involves using analgesics [30,31,32] and sedatives [33]. Gene therapy is being investigated for improving management of chronic pain by sparing the use of drugs with the associated risk of systemic toxicity, opioid addiction and other side effects [34].…”
Section: Applications In Dentistrymentioning
confidence: 99%
“…This will cause a paradigm shift in orthodontic treatment by reducing treatment time with improved results [58]. In addition, gene therapy has shown promising results for controlling the pain of orthodontic tooth movement [32]. Further research may result in the development of gene therapy therapeutic products that can be prescribed in the future to control the pain of orthodontic tooth movement.…”
Section: Applications In Dentistrymentioning
confidence: 99%
“…Orthodontic pain induced by tooth movement is widely considered as a negative consequence of orthodontic treatments 19 . Although the perception of pain is a subjective experience and might vary in individuals, almost all patients complain the discomfort during orthodontic treatment 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, how to alleviate orthodontic pain and elucidate its underlying mechanisms clearly represent one of the major concerns for both patients and orthodontists. Orofacial pain signals induced by tooth movement are received by peripheral nociceptors, transmitted to the first-order neurons in the trigeminal ganglion (TG), conveyed to the trigeminal subnucleus caudalis (Vc) located in the caudal part of medulla oblongata, then relayed to the third-order neurons in the thalamus, and finally perceived by the cortex 19 . Well-grounded experimental observations have documented that both TG and Vc play a crucial role in the transmission of orthodontic pain 16 , 30 .…”
Section: Introductionmentioning
confidence: 99%